Improving Teacher Innovation Through Principal Transformational Leadership and Achievement Motivation - Siti Afriani; Riyan Maulana; Emil Biyansyahna (el-Nizami : Jurnal Manajemen Pendidikan, 2025)
This study aims to formulate concrete efforts in improving teacher innovation based on the study of the relationship between (1) transformational leadership with teacher innovation (2) achievement motivation with teacher innovation (3) transformational leadership and achievement motivation together with teacher innovation. This research was conducted in private junior high schools in Central Bogor Sub-district, Bogor City. This research is a correlational research using quantitative approach. The population in this study were all permanent teachers of private junior high school foundations in Bogor City totaling 165 from 15 private junior high schools and the research sample was 117 people taken with proportional random sampling technique. The results of the study at a significant level of 5% showed that: (1) transformational leadership has a positive effect on teacher innovation with a correlation coefficient ry1 = 0.53 and transformational leadership contributes 27.8% to teacher innovation (2) achievement motivation has a positive effect on teacher innovation with a correlation coefficient ry2 = 0.24 and achievement motivation contributes 5.9% to teacher innovation (3) transformational leadership and achievement motivation together with teacher innovation shown by the correlation coefficient ry12 = 0.54 and transformational leadership and achievement motivation together contribute 29.1% to teacher innovation. Based on the results of the study, it can be concluded that the higher the level of transformational leadership and achievement motivation, the higher the teacher's innovation.